Treatment of a collapse fracture of the anterolateral tibial plateau with a lateral locking plate and the Jail screw technique - Wei Jiang; Xu Liu; Xiang-Ru Kong; Bing Wang; Jian-Ning Sun; Hong-Bin Zheng; Ming Chen (BMC Surgery)
Abstract Background To explore the advantages of a lateral tibial locking plate combined with Jail screw fixation in the treatment of anterolateral tibial plateau collapse fracture (ATPCF). Methods A retrospective analysis was conducted on patients with ATPCFs admitted to our hospital from February 2019 to February 2023. Twenty-six patients were successfully included, including 15 males and 11 females, with an average age of 58.6 ± 7.8 years (range 45–68 years). All fractures were Schatzker type II fractures. After fracture reduction and fixation, a lateral locking titanium plate was placed through the anterolateral approach of the tibial plateau, and two screws of appropriate length were placed in the sagittal direction according to the Jail screw technique. Postoperative evaluation indices included surgery time, fracture healing time, the degree of tibial plateau collapse shown by computed tomography (CT) images at 3 days and 1 year after surgery, and the patient's knee range of motion at 1 year after surgery. The effects of fracture reduction and fixation before surgery, 3 days after surgery and 1 year after surgery were evaluated by the Rasmussen radiological score. The Hospital for Special Surgery (HSS) knee score was used to evaluate the knee joint function of patients at 1 year after surgery. Results The average operation time was 64 ± 6.8 min (range 56–82 min). The fractures healed clinically at 13.8 ± 2.8 weeks (range 12–18 weeks) postoperation. After 15 ± 3.1 months (range 12–19 months) of average follow-up, all the patients were pain-free with a full range of motion and stable knees. At the 1-year postoperative assessment, the CT images showed no secondary collapse of the articular surface, the average knee range of motion was 136.3 ± 2.5° (range, -5° to 135°), the average Rasmussen radiological score was 16.2 ± 0.8 points, and the average HSS knee score was 93.6 ± 3.2 points. Conclusions The fixation of a anterolateral tibial plateau collapse fracture(ATPCF) using a lateral locking plate and the Jail screw technique has achieved good knee joint function, providing a new option for the treatment of ATPCFs. The clinical efficacy is satisfactory in the short term, avoiding secondary articular surface collapse.